2020
DOI: 10.21203/rs.3.rs-27451/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is there any difference in the outcome of geriatric and non-geriatric severely injured patients? – A seven-year, retrospective, observational cohort study with matched-pair analysis

Abstract: Background: The aging population has a tremendous impact on health care. Geriatric trauma is expected to increase due to the lifestyle and activity of the aging population and will be one of the major future challenges in health care. Therefore, the aim of this study was to investigate differences between polytraumatized geriatric and non-geriatric patients regarding 1) mortality, 2) length of stay, and 3) complications with a matched pair analysis. Methods: We included patients older than 17 years with an I… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Overall, our findings match well with previous studies that were performed at a single large level one Trauma center in the TraumaNetzwerk DGU ® : these studies showed very similar trends concerning admissions, injury patterns, and outcome [ 21 , 49 ].…”
Section: Discussionsupporting
confidence: 91%
“…Overall, our findings match well with previous studies that were performed at a single large level one Trauma center in the TraumaNetzwerk DGU ® : these studies showed very similar trends concerning admissions, injury patterns, and outcome [ 21 , 49 ].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, from the data presented by the author, at the time of admission, the elderly patients have higher systolic blood pressure (133/125) and lower base excess (-4.1/-3.6), but the presence of coagulopathy (INR> 1.4) seems with a higher rate (30.2%/20.3%). 24 Unfortunately, the authors did not follow up the elderly trauma patients for the final outcomes of 1 year or 3 years after being discharged from the hospital. Previous studies have found that patients with sepsis, especially the elderly patients, have a third peak in mortality within one year after discharge.…”
Section: Introductionmentioning
confidence: 99%